A scarlet Renaissance : essays in honor of Sarah Blake McHam - McHam, Sarah Blake; Coonin, Arnold Victor (Italica Press studies in art and history., 2013)
Twelve essays by former doctoral students honor the achievements of Sarah Blake McHam as a teacher, mentor and scholar. Topics cover a wide range of Italian art from the trecento to the early seventeenth century, including work in various media, especially Renaissance sculpture. These works share McHam's methodology of applying interdisciplinary evidence to rigorously understand the role art plays within its culture. 117 illustrations. Preface, introduction, notes and bibliography; index.